To determine the surgical outcome of anterior cervical corpectomy and fusion without fixation for ossification of posterior longitudinal ligament - Younus, Syed; Imran, Muhammad; Khan, Ateeq; Basar, Saqib; Sheikh, Daniya (Asian Journal of Neurosurgery, 2019)
Aims: The purpose of our study is to evaluate the surgical outcome in patients undergoing anterior cervical corpectomy without fixation with plates and screws for the treatment of ossification of posterior longitudinal ligament (OPLL). Subjects and Methods: The type of study was case series and was conducted from January 2015 to December 2015 for 1-year duration at the Department of Neurosurgery at a Tertiary Care hospital in Karachi, Pakistan. A total of n = 20 patients (16 men and 4 women; mean age of 57.45 ± 6.4 years [range: 45–68 years]) were included after thorough clinical history and physical examination. Neurological evaluation was done using the Japanese Orthopedic Association (JOA) scoring system. The pre- and post-operative JOA scores were used to calculate recovery rate (RR) of the patients. Radiographic assessment was done using various modalities such as X-ray, computed tomography scan, and magnetic resonance imaging. Surgical outcome and complications were studied and the data were analyzed using SPSS 21. Results: After the uniform follow-up period of 12 months, mean JOA scores improved from 9.1 ± 1.37 preoperatively to 14.3 ± 1.69 postoperatively and mean RR was 67.01 ± 15.5%. All the patients showed successful osseous fusion while one patient did not. Two patients developed cerebrospinal fluid leakage, one patient developed recurrent laryngeal nerve palsy, and one expired due to iatrogenic neurological deterioration. Conclusion: Anterior cervical corpectomy without fi xation with plates and screws is an effective surgical procedure for the treatment of OPLL (for up to three cervical levels of OPLL). It gives good neurological recovery with fewer postoperative complications.
Keywords: Anterior cervical corpectomy; hyperostosis; ossification of posterior longitudinal ligament; spinal fusion; surgical outcome